2019
DOI: 10.7717/peerj.6592
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disruption and divergent microbiota acquisition under extended photoperiod regimens in chicken

Abstract: The gut microbiota is crucial for metabolic homeostasis, immunity, growth and overall health, and it is recognized that early-life microbiota acquisition is a pivotal event for later-life health. Recent studies show that gut microbiota diversity and functional activity are synchronized with the host circadian rhythms in healthy individuals, and circadian disruption elicits dysbiosis in mammalian models. However, no studies have determined the associations between circadian disruption in early life, microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 90 publications
1
37
0
1
Order By: Relevance
“…Light intensity and natural photoperiods may reinforce unique microbiota communities, some of which may also oscillate in synchrony with the host biological rhythms [67,68]. These phenomena have been well documented in mouse studies, and we recently demonstrated that photoperiods influence both microbiota diversity and structure in Hy-line Brown layers [69]. Taken together, the synergistic contribution of cage-free environments is likely to have a more significant contribution to poultry gut microbiota and health than the impact of the soil and litter differences when compared to caged environments.…”
Section: Cage-free Environments Support Higher Chicken Microbiota DIVmentioning
confidence: 65%
“…Light intensity and natural photoperiods may reinforce unique microbiota communities, some of which may also oscillate in synchrony with the host biological rhythms [67,68]. These phenomena have been well documented in mouse studies, and we recently demonstrated that photoperiods influence both microbiota diversity and structure in Hy-line Brown layers [69]. Taken together, the synergistic contribution of cage-free environments is likely to have a more significant contribution to poultry gut microbiota and health than the impact of the soil and litter differences when compared to caged environments.…”
Section: Cage-free Environments Support Higher Chicken Microbiota DIVmentioning
confidence: 65%
“…During the growth of newly hatched chicks, different light regimes cause changes in the circadian rhythm of the clock gene, which in turn changes the structure of intestinal microbes. However, it is unclear how the light cycle affects broiler gut microbiota during fattening (Hieke, Hubert & Athrey, 2019 Bacterial community structure affects insulin synthesis…”
Section: Illumination Affects Bacterial Community Structure and Functionmentioning
confidence: 99%
“…Fecal samples show qualitative similarities with quantitative differences compared to GIT [27,54]. Hieke et al [14] also showed fecal samples are not representative of cecal communities in young layer-type chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, there is a great emphasis on improving poultry health and performance [2][3][4][5]. Notably, the role of gut microbiota in improving performance [6][7][8], welfare [9], and health [4,[10][11][12][13][14], is a topic of intense interest. The gut microbiota is studied intensively in broilers; an NCBI PubMed Central search for "Poultry Gut Microbiota" yielded 2586 research articles within the last five years.…”
Section: Introductionmentioning
confidence: 99%